Answer:
a² + b² = 68
a3 + b3 = 520
Step-by-step explanation:
Given :
a + b = 10 (1)
ab = 16 (2)
A. Find a² + b²
(a + b)² = a² + 2ab + b² (3)
Substitutite the values of (1) and (2) into (3)
(10)² = a² + 2(16) + b²
100 = a² + 32 + b²
Subtract 32 from both sides
100 - 32 = a² + b²
a² + b² = 68
B. a^3 + b^3
(a + b)^3 = a^3 + b^3 + 3ab(a + b)
(10)^3 = a^3 + b^3 + 3*16(10)
1000 = a^3 + b^3 + 480
a^3 + b^3 = 1000 - 480
a3 + b3 = 520
Answer:
30 m
Step-by-step explanation:
You simply add the lengths of all the sides. 3 m is not needed for this.
Answer:
y > ![\frac{5}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B6%7D)
Step-by-step explanation:
Given
5y + 3 > - 7y + 13 ( add 7y to both sides )
12y + 3 > 13 ( subtract 3 from both sides )
12y > 10 ( divide both sides by 12 )
y >
, that is
y > ![\frac{5}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B6%7D)
Answer:12.33333333333
Step-by-step explanation:
8x - 2 = 14x - 76
74 = 6x
12.333 = x